Radiologic bone adaptations on a cementless short-stem shoulder prosthesis - Schnetzke, Marc; Coda, Sebastian; Raiss, Patric; Walch, Gilles; Loew, Markus (Journal of shoulder and elbow surgery, 2016)
This study evaluated the timing and location of radiologic bone adaptations related to shoulder arthroplasty using a single type of cementless short-stem shoulder prosthesis.
Available online 7 November 2015
Gesehen am 20.05.2020